2022
DOI: 10.1186/s12872-022-02454-7
|View full text |Cite
|
Sign up to set email alerts
|

SERPINB1 overexpression protects myocardial damage induced by acute myocardial infarction through AMPK/mTOR pathway

Abstract: Background SERPINB1 is involved in the development of a variety of diseases. The purpose of this study was to explore the effect of SERPINB1 on acute myocardial infarction (AMI). Methods Serum SERPINB1 level of AMI patients was measured for receiver operating characteristic curve analysis. The AMI rat model was constructed to observe myocardial damage, and the H9C2 cell oxygen glucose deprivation (OGD) model was constructed to detect cell viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The Serpin family B member 1 (SERPINB1) with FC of 32.9 and P -value of 0.00085 and adhesion G protein-coupled receptor E5 (ADGRE5) with FC of 0.0054 and P -value of 0.0015 were the most significantly increased and decreased proteins, respectively (Figure c). SERPINB1 belongs to the B-type serum proteins that are involved in various disease processes and reside mainly in the cytoplasm of neutrophils and monocytes . SERPINB1 deficiency can largely ameliorate experimental autoimmune encephalomyelitis, enhance granzyme-mediated mitochondrial damage, and trigger suicidal cell death of pathogenic CD4 T cells …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Serpin family B member 1 (SERPINB1) with FC of 32.9 and P -value of 0.00085 and adhesion G protein-coupled receptor E5 (ADGRE5) with FC of 0.0054 and P -value of 0.0015 were the most significantly increased and decreased proteins, respectively (Figure c). SERPINB1 belongs to the B-type serum proteins that are involved in various disease processes and reside mainly in the cytoplasm of neutrophils and monocytes . SERPINB1 deficiency can largely ameliorate experimental autoimmune encephalomyelitis, enhance granzyme-mediated mitochondrial damage, and trigger suicidal cell death of pathogenic CD4 T cells …”
Section: Resultsmentioning
confidence: 99%
“…SERPINB1 belongs to the B-type serum proteins that are involved in various disease processes and reside mainly in the cytoplasm of neutrophils and monocytes. 43 SERPINB1 deficiency can largely ameliorate experimental autoimmune encephalomyelitis, enhance granzyme-mediated mitochondrial damage, and trigger suicidal cell death of pathogenic CD4 T cells. 44 633 proteins were significantly different between WCB and BAW, with 373 proteins increasing and 260 decreased.…”
Section: Abundance Of Identified Proteinsmentioning
confidence: 99%
“…The HGF/MET receptor mediates the activation of several downstream signaling pathways, the PI3k/AKT/mTOR pathway being among the main ones [82]. Other studies have shown that the AMPK/mTOR pathway is activated by Serpinb1a overexpression in ischemia models and that upstream ADAM causes AKT activation [83,84]. In this regard, we observed an increase in the Hgf gene in the EPI group (Figure 9) and a decrease in Hgf, Serpinb1a, and Adam8 gene expression in the LEV-treated group (Figures 9 and 10B1,B2).…”
Section: Discussionmentioning
confidence: 99%
“…A challenging view indicated that mTOR activation showed diverse dysfunctional effects, including exasperated pathological hypertrophy or misfolded protein accumulation 32 ; however, the inhibition of mTOR activity, particularly the selective inhibition of mTORC1, in addition to the enhancement of autophagy, resulted in reduced cardiovascular damage in response to pressure overload or chronic ischemic injury. 33 34 Autophagy plays a dual role in impaired cardiac tissue, namely, autophagy is cardioprotective, but its attenuation or over-stimulation is harmful to cardiomyocytes, depending on the timing and degree of autophagic activity. 35 Therefore, therapeutic strategies focused on manipulating autophagy in HF patients should consider these effects to fine-tune the autophagic process for optimal benefit.…”
Section: Discussionmentioning
confidence: 99%